Association of two geriatric treatment systems with anti-osteoporotic drug treatment and second hip fracture in patients with an index hip fracture: retrospective cohort study - Rapp, Kilian; Roigk, Patrick; Becker, Clemens; Todd, Chris; Rehm, Martin; Rothenbacher, Dietrich; Konnopka, Claudia; König, Hans-Helmut; Friess, Thomas; Büchele, Gisela (BMC geriatrics, 2024)
BACKGROUND: In Germany, geriatricians deliver acute geriatric care during acute hospital stay and post-acute rehabilitation after transfer to a rehabilitation clinic. The rate patients receive acute geriatric care (AGC) or are transferred to post-acute rehabilitation (TPR) differs between hospitals. This study analyses the association between the two geriatric treatment systems (AGC, TPR) and second hip fracture in patients following an index hip fracture. - METHODS: Nationwide health insurance data are used to identify the rate of AGC and TPR per hospital following hip fracture surgery in patients aged ≥ 80 years. Outcomes are a second hip fracture after surgery or after discharge within 180 or 360 days and new specific anti-osteoporotic drugs. Cox proportional hazard models and generalised linear models are applied. - RESULTS: Data from 29,096 hip fracture patients from 652 hospitals were analysed. AGC and TPR are not associated with second hip fracture when follow-up started after surgery. However, during the first months after discharge patients from hospitals with no AGC or low rates of TPR have higher rates of second hip fracture than patients from hospitals with high rates of AGC or high rates of TPR (Hazard Ratio (95% CI) 1.35 (1.01-1.80) or 1.35 (1.03-1.79), respectively). Lower rates of AGC are associated with lower probabilities of new prescriptions of specific anti-osteoporotic drugs. - CONCLUSIONS: Our study suggests beneficial relationships of geriatric treatment after hip fracture with a) the risk of second hip fractures during the first months after discharge and b) an improvement of anti-osteoporotic drug treatment.